Changes in muscle hypertrophy in women with periodized resistance training - Kraemer, W. J.; Nindl, B. C.; Ratamess, N. A.; Gotshalk, L. A.; Volek, J. S.; Fleck, S. J.; Newton, R. U.; Hakkinen, K. (Medicine & Science in Sports & Exercise, 2004)
Purpose: Adaptations of arm and thigh muscle hypertrophy to different long-term periodized resistance training programs and the influence of upper body resistance training were examined. Methods: Eighty-five untrained women (mean age = 23.1 +/- 3.5 yr) started in one of the following groups: total-body training [TP, N = 18 (3-8 RM training range) and TH, N = 21 (8-12 RM training range)], upper-body training [UP, N = 21 (3-8 RM training range) and UH, N = 19, (8-12 RM training range)], or a control group (CON, N = 6). Training took place on three alternating days per week for 24 wk. Assessments of body composition, muscular performance, and muscle cross-sectional area (CSA) via magnetic resonance imaging (MRI) were determined pretraining (T1), and after 12 (T2) and 24 wk (T3) of training. Results: Arm CSA increased at T2 (~11%) and T3 (~6%) in all training groups and thigh CSA increased at T2 (~3%) and T3 (~4.5%) only in TP and TH. Squat one-repetition maximum (1 RM) increased at T2 (~24%) and T3 (~11.5%) only in TP and TH and all training groups increased 1 RM bench press at T2 (~16.5%) and T3 (~12.4%). Peak power produced during loaded jump squats increased from T1 to T3 only in TP (12%) and TH (7%). Peak power during the ballistic bench press increased at T2 only in TP and increased from T1 to T3 in all training groups. Conclusions: Training specificity was supported (as sole upper-body training did not influence lower-body musculature) along with the inclusion of heavier loading ranges in a periodized resistance-training program. This may be advantageous in a total conditioning program directed at development of muscle tissue mass in young women.